(3TQM eNJUQ Ndjds - (3Ndjd Hf ESMGb Hf ehSi, VjGA GdOjf GdoLrfpOj GdeGdcj GdeUQj,J (B776 (3g` s
(3ChdgG (B:s
(3jHOC HHGH PcQ GdNUGFU s
(3BNQgG (B:s
(3ef LgI Cf ajgG hcGdI abGd s
(3eNJUQ GdTjN Ndjd GfXQ cTa GdXfhf L (B2 (3U`(B1628s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B113s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs